Targeting Adrenomedullin in Oncology: A Feasible Strategy With Potential as Much More Than an Alternative Anti-Angiogenic Therapy - Vázquez, Ramiro; Riveiro, Maria E.; Berenguer-Daizé, Caroline; O’Kane, Anthony; Gormley, Julie; Touzelet, Olivier; Rezai, Keyvan; Bekradda, Mohamed; Ouafik, L’Houcine (Frontiers in Oncology, 2021)
The development, maintenance and metastasis of solid tumors are highly dependent on the formation of blood and lymphatic vessels from pre-existing ones through a series of processes that are respectively known as angiogenesis and lymphangiogenesis. Both are mediated by specific growth-stimulating molecules, such as the vascular endothelial growth factor (VEGF) and adrenomedullin (AM), secreted by diverse cell types which involve not only the cancerogenic ones, but also those constituting the tumor stroma (i.e., macrophages, pericytes, fibroblasts, and endothelial cells). In this sense, anti-angiogenic therapy represents a clinically-validated strategy in oncology. Current therapeutic approaches are mainly based on VEGF-targeting agents, which, unfortunately, are usually limited by toxicity and/or tumor-acquired resistance. AM is a ubiquitous peptide hormone mainly secreted in the endothelium with an important involvement in blood vessel development and cardiovascular homeostasis. In this review, we will introduce the state-of-the-art in terms of AM physiology, while putting a special focus on its pro-tumorigenic role, and discuss its potential as a therapeutic target in oncology. A large amount of research has evidenced AM overexpression in a vast majority of solid tumors and a correlation between AM levels and disease stage, progression and/or vascular density has been observed. The analysis presented here indicates that the involvement of AM in the pathogenesis of cancer arises from: 1) direct promotion of cell proliferation and survival; 2) increased vascularization and the subsequent supply of nutrients and oxygen to the tumor; 3) and/or alteration of the cell phenotype into a more aggressive one. Furthermore, we have performed a deep scrutiny of the pathophysiological prominence of each of the AM receptors (AM1 and AM2) in different cancers, highlighting their differential locations and functions, as well as regulatory mechanisms. From the therapeutic point of view, we summarize here an exhaustive series of preclinical studies showing a reduction of tumor angiogenesis, metastasis and growth following treatment with AM-neutralizing antibodies, AM receptor antagonists, or AM receptor interference. Anti-AM therapy is a promising strategy to be explored in oncology, not only as an anti-angiogenic alternative in the context of acquired resistance to VEGF treatment, but also as a potential anti-metastatic approach.